First report of damage caused by white-spotted stink bug, Eysarcoris ventralis (Westwood) (Hem.: Pentatomidae) on rice in Iran - Mahdi Jalaeian; Sheyvan Zamani; Atousa Farahpour-Haghani (Journal of Crop Protection, 2019)
White-Spotted Stink bug, Eysarcoris ventralis (Westwood) (Hem.: Pentatomidae) was reported as one of the major destructive pests attacking rice worldwide. In Iran, it has been recorded on weeds, grape, alfalfa and wheat. In a survey on rice pests in Guilan province (Northern Iran) during 2017-2018, a large number of adult stink bugs were collected on rice panicles feeding on grains. The sucking on rice grains by adults as well as nymphs caused various symptoms, either empty glumes or spots around the feeding site. This is the first report of the damage symptoms caused by E. ventralis on rice in Iran (Guilan province).